(untitled) (Academicia Globe: Inderscience Research, 2023)
In this article, the development of the main activities of the formation of the spirituality of teenagers, and depending on what kind of moral experience a teenager gains in them, what kind of moral activity he performs, his personality begins to form a certain system of moral skills in teenagers, including work. the relationship formation is also discussed.